GOOD CORPORATE GOVERNANCE PADA NILAI PERUSAHAAN DENGAN KINERJA KEUANGAN SEBAGAI VARIABEL INTERVENING - Esti Damayanti; Wilda Marliana (Program Studi Magister Manajemen Universitas Krisnadwipayana, 2023)
This study aims to determine the partial or simultaneous effect of Good Corporate Governance on Company Value and Financial Performance as an Intervening Variable in Coal Mining Sector Companies Listed on the Indonesia Stock Exchange in 2019-2021. The research design used in this study is a type of quantitative model, the technique used is non-probability sampling with a judgment sampling approach. Data from research is obtained indirectly through intermediary media, generally in the form of evidence, notes or financial reports that have been compiled in archives published by the Indonesia Stock Exchange (IDX). The results in research and analysis prove that Good Corporate Governance (KM) has a positive and significant effect on Firm Value (PBV), Good Corporate Governance (KM) has no effect on Financial Performance (ROA), Financial Performance (ROA) has a positive and significant effect on Value Company (PBV) and Good Corporate Governance (KM) have no effect on firm value (PBV) through the financial performance (ROA) of manufacturing companies in the coal mining sector listed on the Indonesia Stock Exchange. For investors and companies, researchers hope that the results of the research can be used to assist the company in making decisions to be able to increase sales every year and younger companies to get funding for company development.